Nucleophilic addition reactions on the electron-deficient cluster dication [H4Ru4(C6H6)4]2+ : synthesis and structural characterisation of the water-soluble cluster cations [H3Ru4(C6H6)4 (CO)]+ and [H3Ru4(C6H6)4 (OH)]2 - Chérioux, Frédéric; Maisse-François, Aline; Neels, Antonia; Stoeckli-Evans, Helen; Süss-Fink, Georg (My University, 2001)
The electron-deficient (58e) cluster cation [H4Ru4(C6H6)4]2+1 was found to react in aqueous solution with simple nucleophiles to give electron-precise (60e) clusters. With carbon monoxide, the cluster cation [H3Ru4(C6H6)4(CO)]+3 is formed. The reaction with water needs NaN3 as catalyst and yields the cluster dication [H3Ru4(C6H6)4 (OH)]2+4a; the reaction with alcohols leads to the analogous clusters [H3Ru4(C6H6)4 (OR)]2+ (R = Me: 4b, R = Et: 4c, R = PhCH2: 4d, R = Ph: 4e, R = 4-EtC6H4: 4f). The single-crystal X-ray structure analyses of the chloride salts of 3 and 4a reveal a tetrahedral Ru4 metal core. Each ruthenium atom is coordinated by a η6-benzene ligand, while the carbonyl or hydroxo ligands are found as µ3 capping ligands over a triangular face of the Ru4 tetrahedron.